(untitled) (Hematology Meeting Reports, 2009)
The indolent lymphomas include follicular lymphoma (grade 1-2), marginal zone lymphoma, mycosis fungoides, primary cutaneous follicle center lymphoma, and solitary plasmacytoma. Although the follicular lymphomas rarely present with extranodal involvement only, the other indolent lymphomas occur frequently or exclusively with extranodal localizations. Radiation therapy plays a meaningful role in the management of all of these diseases. For patients who present with stage I-IIE disease, that treatment may be with curative intent and expectation. But even patients with stage IIIE-IV disease may achieve meaningful palliation with radiation therapy. This review will consider the role of radiation therapy in the management of extranodal lymphoma in the overall context of treatments available for these diseases.